Resposta imune periapical à medicação intracanal à base de hidróxido de cálcio e selênio - Marcela Carvalho Espaladori (2019)
Endodontic treatment aims to eliminate the microbial contamination of the root canal system (RCS) and is achieved with the use of mechanical instrumentation and chemical irrigation. When resolution in a single session is not possible, the RCS should be filled with intracanal medication to avoid subsequent recolonization. The present study aimed to evaluate the effect of calcium hydroxide, wich is used globally as an intracanal medication, in combination with selenium (CH + Se) as an intracanal medication in teeth with pulp necrosis. The sample consisted of 60 patients requiring endodontic treatment who were divided into groups: without intracanal medication (empty) and with medication; calcium hydroxide (CH), selenium (Se) and calcium hydroxide + selenium (CH + Se) (n = 15). After the coronary opening, three absorbent paper cones were inserted in the initial third of the RCS and maintained for 2min for microbial evaluation. After the cleaning and shaping procedures, new cones were introduced into the RCS, extending 2 mm from the root apex and were kept in the periradicular tissue for 2 min’ to collect the periapical fluid. The collection was also performed 15 days later. Real time PCR was used to quantify the expression of the prokaryotic 16S ribosomal RNA gene. Additionally, the cytokines IFN-γ, TNF-α, IL-1α, IL-17A, IL-10, IL-6 and MCP-1 were also quantified by real-time PCR. The 16S mRNA was evaluated before the cleaning and shaping procedures and 15 days later in the groups treated with or without medication. A significant reduction in the microbial load was observed only in the intracanal group (p <0.05). There was an increase in the gene expression level of the cytokines (T15) TNF-α and IL-10 in the CH+ group compared to the other groups (p <0.05). The expression of IFN-γ mRNA was reduced in the groups treated with the medications (CH, Se, and CH + Se). The findings of the present study indicate that in the case of treatment over multiple sessions, the use of intracanal medication is essential to avoid the recolonization of the RCS. The inclusion of selenium with calcium hydroxide resulted in the potentiation of the anti-inflammatory phase of the periradicular tissues.